2008
DOI: 10.1128/aem.01060-07
|View full text |Cite
|
Sign up to set email alerts
|

Blackbirds and Song Thrushes Constitute a Key Reservoir of Borrelia garinii , the Causative Agent of Borreliosis in Central Europe

Abstract: Blackbirds (Turdus merula) and song thrushes (Turdus philomelos) were found to carry 95% of all spirocheteinfected tick larvae among 40 bird species captured in Central Europe. More than 90% of the infections were typed as Borrelia garinii and Borrelia valaisiana. We conclude that thrushes are key players in the maintenance of these spirochete species in this region of Central Europe.Lyme borreliosis is a tick-transmitted zoonosis caused by spirochete bacteria from the genus Borrelia. This genus comprises 13 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
102
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(115 citation statements)
references
References 15 publications
10
102
3
Order By: Relevance
“…Common blackbirds and thrushes serve as main reservoirs for B. garinii and B. valaisiana in Europe (Humair et al 1998, Hanincova et al 2003b, Taragel'ova et al 2008. The results of our study also support the notion that birds of Turdus spp.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Common blackbirds and thrushes serve as main reservoirs for B. garinii and B. valaisiana in Europe (Humair et al 1998, Hanincova et al 2003b, Taragel'ova et al 2008. The results of our study also support the notion that birds of Turdus spp.…”
Section: Discussionsupporting
confidence: 81%
“…There are several studies reporting the presence of B. afzelii in bird-feeding ticks (Humair et al 1998, Comstedt et al 2006, Kipp et al 2006, Poupon et al 2006, Taragel'ova et al 2008, Franke et al 2010b), although B. afzelii is regarded to be a rodent-associated genospecies in Europe (Humair et al 1999, Hanincova et al 2003a). It has been previously shown that birds do not serve as adequate reservoirs for B. afzelii, and furthermore, that the uptake of avian blood initiates the elimination of B. afzelii in the tick (Kurtenbach et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In Europe, the Eurasian Blackbird carries high parasite loads, not only for avian malaria, but also for other parasites such as Borrelia spp. (Hatchwell et al, 2000;Taragelova et al, 2008). (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…RFLP analysis revealed that strains of this subtype were genetically highly homogeneous (Marconi et al, 1999). Furthermore, ospA type 4 strains form a distinct ecotype within B. garinii and utilize rodents as reservoir hosts (Hu et al, 1997;Huegli et al, 2002), while other subtypes of B. garinii are transmitted by birds (Dubska et al, 2009;Hanincová et al, 2003b;Taragel'ová et al, 2008). In Asia, NT29 and related strains also comprise a rodent-associated ecotype within B. garinii, but their relationship to ospA type 4 strains from Europe remained unclear as European and Asian B. garinii not only differed in their ospA pattern, but also showed differences in the RFLP pattern of the 5S-23S intergenic spacer (reviewed by Miyamoto & Masuzawa, 2002).…”
mentioning
confidence: 99%